Ion acceleration enhancement in laser-generated plasmas by metallic doped hydrogenated polymers - Angela Maria Mezzasalma; Francesco Caridi; Antonio Borrielli; Lorenzo Torrisi (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2009)
Laser-generated plasmas in vacuum were obtained by ablating hydrogenated polymers at the Physics Department of the University of Messina and at the PALS Laboratory in Prague. In the first case a 3 ns,532 nm Nd:Yag laser, at 1010 W/cm2 intensity was employed.In the second case a 300 ps, 438 nm iodine laser, at 5x1014W/cm2 intensity was employed. Different ion collectors were usedin a time-of-flight configuration to monitor the ejected ions from theplasma at different angles with respect to the direction normal tothe target surface. Measurements demonstrated that the mean ionvelocity, directed orthogonally to the target surface, increases forablation of polymers doped with metallic elements with respect tothe nondoped one. The possible mechanism explaining theresults can be found in the different electron density of theplasma, due to the higher number of electrons coming from the dopingelements. This charge enhancement increases the equivalent ionvoltage acceleration, i.e. the electric field generated in the non-equilibrium plasma placed in front of the ablated target surface.